Particulate blood analogues reproducing the erythrocytes cell-free layer in a microfluidic device containing a hyperbolic contraction - Calejo, Joana (2016)
The interest in the development of blood analogues has been increasing recently as a consequence of the increment in the number of experimental hemodynamic studies and the difficulties associated with the manipulation of real blood in vitro because of ethical, economical or hazardous issues. Although one-phase Newtonian and non-Newtonian blood analogues can be found in the literature, there are very few studies related to the use of particulate solutions in which the particles mimic the behaviour of the red blood cells (RBCs) or erythrocytes. One of the most relevant effects related with the behaviour of the erythrocytes is a cell-free layer (CFL) formation, which consists in the migration of the RBCs towards the center of the vessel forming a cell depleted plasma region near the vessel walls, which is known to happen in in vitro microcirculatory environments. Recent studies have shown that the CFL enhancement is possible with an insertion of contraction and expansion region in a straight microchannel. These effects are useful for cell manipulation or sorting in lab-on-chip studies. In this experimental study we present particulate Newtonian and non-Newtonian solutions which resulted in a rheological blood analogue able to form a CFL, downstream of a microfluidic hyperbolic contraction, in a similar way of the one formed by healthy RBCs.